The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4028/www.scientific.net/amr.343-344.618
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Detection of Traces of Potentially Allergenic Soybean (<i>Glycine max</i>) in Food Matrices

Abstract: As an important source of food ingredients, it is necessary for soybean detection in foods because it was reported as one of the “big 8” food allergens. In this report, a PCR-based method was developed enabling the detection of even small traces of potentially allergenic soybean traces in food products. Soybean-specific primer was designed based on Gly m Bd 28K, one of the major allergens in soybean. The assay was applied to a wide range of food matrices and the detection limit was 0.01% (100ppm) for spiked pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Consequently, they were applied in multiplex PCR analysis. The detected allergen-specific PCR fragments can be considered as novel DNA markers as they are distinguished from the allergen DNA markers described previously for soybean and GMO [ 9 , 19 , 20 , 21 ]. These DNA markers are 86 bp and 98 bp amplicons for Gly m Bd 28K; 129 bp, 118 bp, and 122 bp amplicons for Gly m Bd 30K; 135 bp amplicon for lectin as well as 114 bp and 172 bp amplicons for epsps gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they were applied in multiplex PCR analysis. The detected allergen-specific PCR fragments can be considered as novel DNA markers as they are distinguished from the allergen DNA markers described previously for soybean and GMO [ 9 , 19 , 20 , 21 ]. These DNA markers are 86 bp and 98 bp amplicons for Gly m Bd 28K; 129 bp, 118 bp, and 122 bp amplicons for Gly m Bd 30K; 135 bp amplicon for lectin as well as 114 bp and 172 bp amplicons for epsps gene.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantage of the PCR technique is its specificity, reliability, and rapidity allowing the detection of trace amounts of allergens in processed products. The end-point and real-time PCR methods have been reported for the detection of soybean allergens, namely Gly m Bd 28K [ 19 ], Gly m Bd 30K [ 20 ], lectin [ 21 ]. The comparison of ELISA and PCR methods using soya food products showed that the sandwich ELISA had the lowest detection limit of 0.05 ppm, but only identified soy in five out of the eight products.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic markers for identifying Gly m Bd 28 K free cultivars have not been applied so far. However, both cDNA sequence of the allergen gene (TSUJI et al, 2001) as well as a PCR primer for allergen detection (WANG et al, 2012) have been published which could support the development of an efficient marker system for selection purposes.…”
Section: Gly M Bd 28 Kmentioning
confidence: 99%